Investigation of the Potential Pharmacological Substance Basis and Mechanism of Action of Xuantu Granules in Treating Diabetic Kidney Disease Based on UHPLC-Q-Exactive-HRMS and Bioinformatics - Fan, Jingna; Kong, Chang; Yu, Bin; Wang, Rong; Qi, Zhenqiang (Combinatorial Chemistry & High Throughput Screening, 2025)
ObjectiveThe objective of this study is to analyze and identify the main chemical components and blood-absorbed components of Xuantu Granules and predict their pharmacological substance basis and mechanism in the treatment of DKD.MethodsA DKD rat model was established by feeding SD rats a high-fat and high-sugar diet and administering intraperitoneal injections of streptozotocin (STZ). The therapeutic effect of Xuantu granules was evaluated. Drug-containing serum was prepared after gavage, and the major chemical components of Xuantu Granules and the drug-containing serum were detected using UHPLC-Q-Exactive-HRMS. Blood-absorbed components were identified based on retention time, mass-to-charge ratio, and MS/MS spectrum. Blood-absorbed components’ target proteins were searched using the CTD, SwissTarget, BindingDB, and TargetNet databases. DKD disease target genes were screened from the GEO database using WGCNA. A “bioactive blood-absorbed component-target-disease” PPI network was constructed using Cytoscape software, and the key clustering subnetworks were identified by MCODE plugin. GO functional analysis and KEGG pathway enrichment analysis were performed on subnetworks.ResultsXuantu Granules lowered fasting blood glucose, improved renal function, reduced proteinuria, and improved renal tissue pathological changes in DKD rats. 36 chemical components were identified, among which 12 compounds, including β -Carboline-1-propionic acid, Morin, Afzelin, Schizandrin, Gomisin A were identified as blood-absorbed components. Bioinformatics analysis indicated that AKT1, TNF, TP53, IL6, SRC, IL1B, EGFR, JUN, BCL2, and CASP3 might be the main therapeutic targets. The involved pathways included the IL-17 signaling pathway, PI3K-Akt signaling pathway, AGE-RAGE signaling pathway in diabetic complications and so on.ConclusionXuantu Granules may exert therapeutic effects on DKD through multiple targets and pathways.
Keywords: Xuantu granules